2019
DOI: 10.1532/hsf.2343
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Giant Pulmonary Aneurysm with Left Lung Compression: A Case Report with Insights from the Literature

Abstract: Pulmonary artery aneurysm (PAA) is a rare condition that results from several pathologies. Here, we report a case of a rare giant PAA accompanied by left lung compression due to recurrent chest tightness for >13 years. Through this case and review of the literature, we explore the treatment options to improve the diagnosis and treatment of PAA. We found that patients with PAA may survive longer even if they also have pulmonary hypertension. In addition, it is recommended that if a PAA diameter is &g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Moreover, this is the second largest PAA (diameter of 14 cm) ever reported in the literature. A previous study by Fan et al reported the largest PAA, with a diameter of 17 cm [13].…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, this is the second largest PAA (diameter of 14 cm) ever reported in the literature. A previous study by Fan et al reported the largest PAA, with a diameter of 17 cm [13].…”
Section: Discussionmentioning
confidence: 89%